Health-related behavior patterns of cancer patients determined by socio-demographic variables - Humeniuk, Ewa; Dąbska, Olga; Pawlikowska-Łagód, Katarzyna; Matuska, Małgorzata (Polish Journal of Public Health, 2018)
Introduction. Health practices have been a subject of theoretical and empirical discussions among experts from various fields of knowledge. They are analyzed more and more closely, regarding their connection with specific diseases. Because cancer is one of the main causes of death in Poland, it is very important to learn more about pro-health behaviors undertaken by cancer patients.Aim. An attempt was made to establish if pro-health activities and their separate categories regarding cancer patients are preconditioned by socio-demographic variables.Material and methods. The research was conducted on the group of 100 cancer patients. Diagnostic poll method, survey technique was used when conducting this study. Health Behavior Inventory (HBI) by Zygfryd Juczyński was the research tool. STATISTICA 12 and Microsoft Office Excel were used to analyze the gathered data. Statistical significance of p